Raman optical time domain reflectometry for aircraft fire-overheat detection and monitoring - Odic, Richard Marie (Cranfield University, 2004)
The analysis of the development context for a distributed temperature detection system in an aircraft cargo compartment and the review of candidate technologies stressed the advantages of using the spontaneous Raman scattering principle with a signal processing in the time domain. Simultaneously, the wished detection performance defines the hardware specifications of the system. For the "Cargo Compartment Fire Detection and Extinguishing" application, several design parameters were identified; namely: the spatial and sampling resolution, the temperature accuracy and its resolution, the possible sensing element length for a given peak optical power per pulse, the refreshment time to get a temperature profile over the sensing element length, the operating/survival temperature ranges and the mechanical constraints at the sensing element in operation or during installation and the possibility to discriminate an optical fibre break from an increase in temperature. To reject the noise generated and amplified by the Avalanche Photo-Diodes (APD) and by the cascaded amplification modules, the numerical signals were . processed using digital filters. The detection system has also to early detect a fire while rejecting fire-like events. Its detection performances are, namely: a temperature profile refreshment time of 3s, a temperature resolution of± 1 °C around the alarm signal, a spatial resolution of 1.3m for a sensing element length of 500m. The detection of a temperature increase is a spatial analysis organized through specific algorithms. These algorithms involve processing the temperature time derivative, the spatial gradient, the variation of danger surfaces, an analysis of the temperature spatial frequencies and the calculation of the power spectral density and of the temperature covariance matrix. Fire tests were performed and the optical fibre within a protective stainless steel tube was connected to a control unit to monitor the danger situation over an aircraft cargo compartment.